Residual lignin from biomass pretreatment for 2G ethanol production as an adsorbent in dye removal - Avancini, Anita Ribas; Lemões, Juliana Silva; Matoso, Ester Schiavon; Cruz, Nidria Dias; Silva, Sérgio Delmar dos Anjos; Silva, Cláudia Fernanda Lemons (Ciência e Natura, 2019)
Liquid waste from some industrial activities generates a serious environmental impact due to the presence of dyes. However, during the production process of second-generation ethanol, a lignin-rich residue is generated, which may be able to absorb the dyes in the waste. The goal of this work was to test the potential of lignin as a dye-removal adsorbent. Two quantities of precipitated lignin (200 and 500 mg) were tested as adsorbents by contact with Methylene Blue, Eriochrome Black T, and Bromocresol Green dyes. Kinetics curves for the adsorption capacity (Q) of lignin quantities were constructed and the percentage of removal of each dye was calculated. The Q of the three dyes increased with contact time and was higher in the 200-mg treatment; however, the strongest dye removal was presented by the 500-mg treatment. The maximum removal achieved was 84.77% with 500 mg lignin in the methylene blue solution and the minimum was 21.32% with 200 mg in the Bromocresol green solution. Therefore, it is concluded that lignin has potential as an adsorbent, as increased quantities are more efficient in removing dyes.